The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jccs.201800275
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, fluorescence imaging, and cytotoxicity studies of a uracil‐based azo derivative and its metal complexes

Abstract: A uracil‐based heterocyclic azo derivative was prepared by coupling diazotized 5‐aminouracil with 2‐naphthol. This ligand, viz., 1‐(2,4‐dioxopyrimidine‐5‐yl)‐azo‐naphth‐2‐ol (HNAP), was used as a precursor for the synthesis of a series of complexes with manganese(II), cobalt(II), nickel(II), copper(II), and zinc(II) ions. Various physicochemical measurements UV–Visible, Infrared (IR), 1H NMR, 13C Nuclear Magnetic Resonance (NMR), and electron spin resonance (ESR) spectral studies were employed to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The proliferation inhibitory effect of all targeted compounds against tumor cells was determined using the MTT assay . The screening results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proliferation inhibitory effect of all targeted compounds against tumor cells was determined using the MTT assay . The screening results are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…MTT assay: Cells were seeded in 96‐well plates and incubated in the CO 2 (5%) incubator at 37°C. When the cells adhered, compounds at a concentration of 20 μmol/L were added to each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low band intensity that belongs to complexes caused the decreasing electron density of the ligand (Yamgar et al, 2009) The free ligand exhibits an emission maximum at 569 nm with excited at 530 nm in DMSO, and the Cu(II) complex noted an emission band at 565 nm as in Figure 4: but, at the same excited band (530 nm), the Co(II) and Ni(II) complexes possess no luorescence. The chelation of the metal with ligand performing the posing of the non luorescent complex; consequently, the luorescent intensity is decreased and promotes quenching (Philip et al, 2019) NMR Studies…”
Section: )mentioning
confidence: 99%
“…The 2H-chromene (2H-1-benzopyran) moiety is one of the most important heterocycles detected in many biologically active natural products and in synthetic compounds (Kolokythas et al, 2007;P et al, 2009;Schweizer and Meeder, 1977) 2H-chromenes were reported to display signi icant antioxidant (Kwak et al, 2006) , antiviral (Martínez-Grau and Marco, 1997) , antimicrobial (Li et al, 2018) anti-in lammatory (Gebhardt et al, 2007) and antifungal (Chanu et al, 2017) properties, in addition to their interesting applications as highly effective luorescent dyes (Moorthy et al, 2006) Furthermore, several metal complexes of chromene derivatives possess antimicrobial (Soliman et al, 2016) DNA cleavage activities (Prabhakara et al, 2015) and photoluminescence properties (Aazam et al, 2012) . Azo compounds and their complexes are highly important due to their applications as textile dyes , Zhigang et al (2009) indicators (Abbas et al, 2018) , medicinal importance (Philip et al, 2019) and are also inhibition of DNA, RNA and protein cre-ation (Park et al, 2007) In the present study, we display the synthesis and characterization of Co(II), Cu(II), and Ni(II) complexes with new azo-linked chromene ligand (AH). The newly ligand and its complexes were examined for their antibacterial potency against some types of gram-positive and negative bacteria; DNA cleavage activity, and also luorescence properties…”
Section: Introductionmentioning
confidence: 99%